From Absolute Poverty to Participatory Poverty Assessment and Back Again? A Critique of Poverty Scorecard through a Case Study from Khyber Pakhtunkhwa, Pakistan. (December 2020) - Owais, Syed
This paper critiques the poverty scorecard (PSC), a monetary-based tool for measuring poverty that has been adopted by community development programmes and participatory non-governmental organizations (NGOs) in 66 countries including Pakistan. Drawing on 15 interviews and five focus group discussions conducted with the staff members and community members of Frontier Organization for Rural Development, a participatory NGO in Pakistan, I argue that it uses clouds intra-household power and resources distribution thereby furthering gender, class, and ethnic inequalities. Instead of solely relying on the PSC, the paper suggests supplementing it with participatory methods.